ABOUT THE APPLICATION AND TEST RESULTS IN THE THEORY KODAM JAYA USING VISUAL BASIC VERSION 6.0 - Kellek Kurniawan; Ire Puspa Wardhani, SKom, MMSI (Jurnal Sistem Informasi, 2003)
Use of computer applications is very useful because with this then about the makers did not need to waste time and can perform calculations quickly and accurately because of the many applicants who take exams test this theory.